1950
DOI: 10.1017/s0007485300024408
|View full text |Cite
|
Sign up to set email alerts
|

A new systemic Insecticide bis (bis dimethylamino phosphonous) anhydride

Abstract: Schrader (1947a), working on the preparation and insecticidal evaluation of certain phosphorus and fluorine compounds, developed some that were shown to be systemic. A systemic compound is one that is absorbed by the plant and translocated in the sap so that parts of the plant other than those treated become toxic to sucking insects. Schrader referred to these substances as agents for the chemotherapy of living plants. One of them was bis(bis dimethylamino phosphonous)anhydride, which was prepared by him in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

1950
1950
1969
1969

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 4 publications
2
10
0
1
Order By: Relevance
“…KO appreciable progress in the development of systemic insecticides seems to have been made until the work of Schrader and Kukenthal became generally known as a result of reports by Martin (1947), Martin & Shaw (1948) and Schrader (1948). Various workers have been able to substantiate many of the claims made by Schrader (Bennett & Martin, 1947; Bennett, Martin, Stringer & Woodcock, 1948; David, 1949; David & Kilby, 1949; Ripper, Greenslade & Hartley, 1950). The present paper gives further information concerning the systemic properties of three compounds developed by Schrader and Kukenthal and also about sodium fluoroacetate which has only recently been shown to possess potent systemic insecticidal activity (David, 1 9 5 0~) .…”
Section: Introductionsupporting
confidence: 56%
“…KO appreciable progress in the development of systemic insecticides seems to have been made until the work of Schrader and Kukenthal became generally known as a result of reports by Martin (1947), Martin & Shaw (1948) and Schrader (1948). Various workers have been able to substantiate many of the claims made by Schrader (Bennett & Martin, 1947; Bennett, Martin, Stringer & Woodcock, 1948; David, 1949; David & Kilby, 1949; Ripper, Greenslade & Hartley, 1950). The present paper gives further information concerning the systemic properties of three compounds developed by Schrader and Kukenthal and also about sodium fluoroacetate which has only recently been shown to possess potent systemic insecticidal activity (David, 1 9 5 0~) .…”
Section: Introductionsupporting
confidence: 56%
“…B. brassicae was studied in pioneer attempts at integrated control by Ripper (1944), who demonstrated the selective action of nicotine, and by Ripper, Greenslade & Hartley (1950) who concluded that the selective action of the systemic insecticide schradan preserved natural enemies which then prevented immediate aphid resurgences such as those caused by the non-selective contact insecticide parathion.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the anhydride is absorbed by the leaves of certain plants and translocated in insecticidal quantities (Ripper, Greenslade & Hartley, 1950;David, 1951). A similar effect has not been reported with the oxide, and indeed it seems possible that if absorption does occur through the leaves the material might be so 14-2 readily lost again by vaporization that it would not be transported very far from the point of absorption.…”
Section: Penetration and Translocation Following Application Of The Omentioning
confidence: 84%